Innovation, finance, and economic growth: An agent-based approach - Giorgio Fagiolo; Daniele Giachini; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
This paper extends the endogenous-growth agent-based model in Fagiolo& Dosi (2003) to study the finance-growth nexus. We explore industries where firms produce a homogeneous good using existing technologies, perform R&D activities to introduce new techniques, and imitate the most productive practices. Unlike the original model, we assume that both exploration and imitation require resources provided by banks, which pool agent savings and finance new projects via loans. We find that banking activity has a positive impact on growth. However, excessive financialization can hamper growth. Indeed, we find a significant and robust inverted-U shaped relation between financial depth and growth. Overall, our results stress the fundamental (and still poorly understood) role played by innovation in the finance-growth nexus.
Keywords: C63; G21; O30; O31; 330; Agent-based Models; Innovation; Exploration vs. Exploitation; Endogenous Growth; Banking Sector; Finance-Growth Nexus